EVALUASI KAPASITAS DRAINASE PERKOTAAN DI JALAN GOTONG ROYONG: STRATEGI ADAPTASI TERHADAP RISIKO BANJIR AKIBAT URBANISASI - Nur Azizah Affandy; Ahmad Permay Ainun Rizqy Didan; Bobby Damara (Jurnal Ilmiah MITSU (Media Informasi Teknik Sipil Universitas Wiraraja), 2026)
Urban drainage systems play a crucial role in managing stormwater runoff to prevent flooding, particularly in highly urbanized areas like Gotong Royong Street. Urbanization and land-use changes have increased the risk of surface runoff, while existing drainage channels often fail to accommodate rising flood discharges. This study aims to evaluate the capacity of existing drainage channels against the design flood discharge using hydrological and hydraulic analyses. The methods include calculating the design flood discharge using the rational formula and performing hydraulic analysis with Manning’s equation to assess channel capacity. The results indicate that the drainage channels at points 1 and 2 are insufficient to handle the design flood discharge for 2-year and 5-year return periods, while channels at points 3 and 4 meet the capacity requirements only for the 2-year return period. This capacity mismatch highlights the need for channel upgrades to mitigate potential flooding. Recommendations for future research include developing GIS-based simulation models to comprehensively identify flood-prone areas and assessing the impact of land-use changes on drainage systems. This study contributes to the planning of more adaptive drainage infrastructure in response to dynamic hydrological conditions.